Il Centrokappa e la mostra ’Il Design italiano negli anni ’50’ - Iannello, Matteo (Opus Incertum, 2024)
In September 1977, the exhibition Il design italiano negli anni ’50 was inaugurated in Milan. Hosted within the Centrokappa spaces in Noviglio, located inside the Kartell factory, it was organized by the Centrokappa collective, founded in Milan in 1972 by Valerio Castelli. The exhibition aimed to investigate and revisit the historical moment in which the current Italian design context began to take shape. Rather than following a historical approach, the exhibition presented the coexistence of different moments of research. A unitary project, the result of a collective work, was presented through six distinct sections specifically ordered: industrial design, graphics, objects, textiles and fashion, furniture, reconstruction of environments. The exhibition layout, curated by Andrea Branzi, Valerio Castelli, Masayuki Matsukaze, Paola Navone, and Valentino Parmiani, unfolded across multiple levels articulated around the large central atrium marked at the top by the neon “Spatial Concept” created in 1951 by Lucio Fontana for the 9th Milan Triennale and reconstructed for the occasion. The exhibition represented the first significant critical re-examination of that vibrant period. Its importance extended beyond its rich yet necessarily partial historical-artistic content. Instead, its true merit lay in having opened and fueled a debate around the theme of industrial design, and its role within contemporary society.